Incidence of underlying CAD in chest pain patients with intermediate risk for ACS: a retrospective analysis - Abigail Coutinho; Faith Oluwaseun Williams; Ibukunoluwa Ogunbowale; Mohamed Azmi Kasmi Elmetwali; Abdul Basit Malik; Ramabala Vuyyuru; Sayak Roy; Taiwo Ikuesan; Pradeep Singh; Francis Castaneda; Marifel Rojo (Clinical Medicine)
Introduction: Coronary artery disease (CAD) is a leading cause of mortality throughout the world if not detected and treated properly. Finding the correct candidate for further cardiological investigations is a big dilemma when patients present to the emergency department (ED) with chest pain. The grey zone is the one that comes with the most intermediate-risk factors.1 As per data, it is noted that ∼2% of patients presenting to the ED with acute coronary syndrome (ACS) are mistakenly discharged, leading to a significant increase in risk.2 This can cause a twofold rise in 30-day morbidity and mortality, underscoring the critical importance of our diagnostic approach. The approach involves obtaining a good clinical history, carrying out a physical examination, performing a 12-lead electrocardiography (ECG), and measuring cardiac biomarkers ideally within 10 min of arrival in the ED.3 To effectively rule out acute myocardial infarction, it is essential to have normal troponin levels and a non-ischaemic ECG.4To capture patients who will need further cardiological investigations early, a telephone chest pain clinic has been introduced. Patients whose histories were suggestive of cardiac-sounding chest pain with intermediate risk factors (as suggested by our hospital pathway) are referred to this clinic for further rapid outpatient workup. Methods: We meticulously analysed data collected between 5 April 2024 and 4 December 2024, from the telephone chest pain clinic referral triage sheet of a single centre from south-east London, ensuring a comprehensive and reliable dataset for our study. Complete patient anonymity was maintained for data protection.One hundred thirty-five referrals from our ED and medical same-day emergency care (SDEC) department were made to this clinic, 18 of whom did not attend. Of the remaining 117 patients, 61 with baseline troponin levels and standard ECG patterns were accepted for further investigations.We used online software5 to estimate the mean with 95% confidence intervals (CIs) for baseline continuous variables, and we represented the categorical variables as percentages out of the total available dataset. Results: Our analysis revealed a significant finding: 32.78% of patients (20 out of 61) had some degree of positive ischaemic findings in their follow-up investigations, either inducible ischaemia or established coronary artery disease on either computed tomography (CT) coronary angiography or invasive coronary angiography. This underscores the importance of our research. The summaries of baseline characters, and intermediate risk factors used are depicted in Table 1. Conclusion: A significant proportion of patients can have underlying CAD, irrespective of their normal troponin level and normal ECG. History-taking and proper referral of these patients with intermediate risk factors to an early telephone CP clinic for early outpatient follow-up will not only help detect the burden of smouldering CAD in society, but also avoid unwanted hospital admissions and lessen the duration of stay.